Antiphospholipid syndrome nephropathy - WANG Xiao-ling; LI Rong-da; PENG Jia-qing (Linchuang shenzangbing zazhi)
Anti-phospholipid syndrome(APS) is an autoimmune disease that can involve multiple systems and is characterized by recurrent arterial and/or venous thrombosis, abnormal pregnancy, and persistent presence of anti-phospholipid antibodies. APS can lead to a variety of related diseases in the kidney, among which the diseases occurring in the kidney itself and glomerulus are usually called antiphospholipid syndrome nephropathy(APSN). The correct diagnosis and treatment of APSN are of great significance to improve the prognosis of patients. At present, less attention has been paid to this research in our country. Therefore, in order to promote clinicians’ understanding and attention to APSN, we will make a review on the research progress of APSN.